ASSOCIATION OF BIOFILM PRODUCTION AND TWITCHING AND SWARMING MOTILITY OF CLINICAL ISOLATES OF ACINETOBACTER BAUMANNII - Ranin, Jovana L; Šmitran, Aleksandra; Gajić, Ina (Medicinski podmladak, 2019)
Abstract Introduction: Acinetobacter baumannii is a ubiquitous Gram-negative bacillus that has emerged as one of the most important cause of healthcare-associated infections primarly due to multidrug resistance and its ability to survive within biofilm on nonliving objects. Acinetobacter posses pili that mediates its adherence to abiotic surfaces and certain types of motility such as twitching and swarming. Aim: The aim of this study was to determine the capacity of the biofilm production of A. baumannii and the twiching and swarming motility. Material and methods: A total of 128 strains of A. baumannii isolated from blood (34), wound swabs (35), respiratory tract (39) and other clinical materials (20) were included in the study. Biofilm-producing ability was tested in the microtiter plates at 26°C and 37°C for 24 hours incubation period and at 37°C for 48h incubation as well. The presence of the pili was determined by the testing of the twitching and swarming motility in a semi-solid nutrient medium. Results: More than 90% of isolates showed moderate or strong biofilm production capacity regardless of the experimental conditions. Decreasing in biofilm production was noticed in the group of strong biofilm producers (p<0.001) during prolonged incubation time (48h). During the 24-hour incubation period, wound and respiratory isolates were significantly more frequent in the group of strong biofilm producers compared to blood and other isolates. No correlation between specific types of motility and biofilm production was noticed. Conclusion: The biofilm production remained stable under the tested experimental condition. There was no decisive influence of pili on this virulence factor. Keywords: Acinetobacter baumannii, biofilm, motility, pili